Case Report: Neurobrucellosis Presenting as Malignancy - Salcedo, Andrea S. (2024)
Neurobrucellosis, caused by Brucella species, is a zoonotic infection that may involve the central nervous system. Although uncommon, it can manifest as a solitary intracranial mass. We report a case of neurobrucellosis in a 25-year-old woman from Peru who presented with headache, weight loss, and right-side hemiparesis and paresthesia. A contrast-enhanced magnetic resonance imaging scan revealed an intracerebral mass in the left temporal lobe. Serum testing subsequently were positive. Brain biopsy demonstrated non-necrotizing granulomas without malignant cells. Neurobrucellosis should be considered in the differential diagnosis of brain space occupying lesions in endemic countries. Copyright